Handbook of research on urban and humanitarian logistics - Gonzalez-Feliu, Jesus (Business Science Reference, 2019)
"This book examines urban logistics and resilience with a focus on sustainable urban logistics, humanitarian logistics in urban areas (both for crisis or long-term) and planning for resilient urban development"--